Offshore Renewable Energy Expansion, Marine Biodiversity Risk, and the Effectiveness of Marine Spatial Planning in Taiwan: A Spatial–Governance Assessment - Chengyu Hu; Jiabin Lin; Yiche Shih (Journal of Marine Science and Engineering, 2026)
By integrating ecological spatial data, offshore wind energy development zones, and the marine spatial planning (MSP) framework, it is possible to assess the relationship among Taiwan’s offshore renewable energy development, risks to marine biodiversity, and the effectiveness of marine spatial planning. The study adopts a mixed-method spatial–quantitative research design that integrates geospatial modelling, ecological risk assessment, spatial conflict analysis, and governance evaluation for quantification of biodiversity exposure to offshore wind infrastructure. Spatial overlay analysis is employed in the identification of geographic areas where offshore wind development intersects with high biodiversity vulnerability zones. Quantitative spatial indicators are used to assess the extent to which MSP reduces biodiversity exposure to offshore renewable energy infrastructure. The analytical framework integrates two parallel modelling domains including the ecological risk modelling domain and the spatial governance effectiveness domain. The spatial analysis of biodiversity vulnerability across Taiwan’s analyzed offshore areas revealed a BVI range of 0.12 to 0.88. The mean BVI value was 0.51 (S.D. = 0.18). The results further show that over 47% of the analyzed EEZ falls into high and very high vulnerability classes. The total offshore wind area located within high-risk and very high-risk zones accounted for 38% of the wind farm footprint. Smaller proportions occupy very low and low-risk zones, accounting for 7.1% and 21.4%, respectively, while 32.1% of wind infrastructure is in moderate-risk areas. Overlaying MSP boundaries with biodiversity risk zones showed that 62% of high-risk biodiversity areas are encompassed within MSP-designated protection, leaving 38% of high-risk zones unprotected. The findings show that biodiversity preservation and offshore wind development are not mutually exclusive but are rather dependent on efficient spatial planning, integrated governance, and flexible management to maintain sustainability.